Practice based design for learning at work (doi: 10.3991/ijac.v1i2.620) - Lundin, Johan; Svensson, Lars; Lundh-Snis, Ulrika; Pareto, Lena (International Journal of Advanced Corporate Learning (iJAC), 2008)
Designing for learning at work in a manner that embraces the rich situatedness of practice involves a number of challenges in bridging normative and descriptive perspectives, as well as closing the gap between IS design theory and practice. In this paper, we propose a grounded approach that combines influence from learning theories with studies of existing learning practices. This approach could result in learning models, constituted of a sequence of learning activities that outlines the didactics of the workplace. The arguments are based on the empirical findings from an action-oriented research project in collaboration with six SME:s, and are illustrated through a e-learning model called â??The Competence Kick-off